Association Between Opioid Agonist Therapy and Testing, Treatment Uptake, and Treatment Outcomes for Hepatitis C Infection Among People Who Inject Drugs: A Systematic Review and Meta-analysis. (24th May 2020) - Grebely, Jason; Tran, Lucy; Degenhardt, Louisa; Dowell-Day, Alexander; Santo, Thomas; Larney, Sarah; Hickman, Matthew; Vickerman, Peter; French, Clare; Butler, Kerryn; Gibbs, Daisy; Valerio, Heather; et al.
Abstract: Background: People who inject drugs (PWID) experience barriers to accessing testing and treatment for hepatitis C virus (HCV) infection. Opioid agonist therapy (OAT) may provide an opportunity to improve access to HCV care. This systematic review assessed the association of OAT and HCV testing, treatment, and treatment outcomes among PWID. Methods: Bibliographic databases and conference presentations were searched for studies that assessed the association between OAT and HCV testing, treatment, and treatment outcomes (direct-acting antiviral [DAA] therapy only) among PWID (in the past year). Meta-analysis was used to pool estimates. Results: Of 9877 articles identified, 22 studies conducted in Australia, Europe, North America, and Thailand were eligible and included. Risk of bias was serious in 21 studies and moderate in 1 study. Current/recent OAT was associated with an increased odds of recent HCV antibody testing (4 studies; odds ratio (OR), 1.80; 95% confidence interval [CI], 1.36–2.39), HCV RNA testing among those who were HCV antibody–positive (2 studies; OR, 1.83; 95% CI, 1.27–2.62), and DAA treatment uptake among those who were HCV RNA–positive (7 studies; OR, 1.53; 95% CI, 1.07–2.20). There was insufficient evidence of an association between OAT and treatment completion (9 studies) or sustained virologic response following DAA therapy (9 studies). Conclusions: OAT can increase linkage to HCV care, including uptake of HCV testing and treatment among PWID. This supports the scale-up of OAT as part of strategies to enhance HCV treatment to further HCV elimination efforts. Abstract : Opioid agonist therapy (OAT) was associated with increased hepatitis C virus (HCV) testing and treatment among people who inject drugs but not treatment completion or sustained virologic response. This supports the scale-up of OAT as part of strategies to enhance HCV treatment to further elimination efforts.